SURVEY ON FISH DISEASES ON COBIA AND GROUPER OF MARINE FISH CAGE CULTURE IN NAM DU ISLANDS, KIEN HAI DISTRICT, KIEN GIANG PROVINCE - Khanh, Ly Van; Phu, Tran Minh; Hai, Tran Ngoc; Dung, Tu Thanh (Vietnam Journal of Marine Science and Technology, 2017)
The study was conducted to investigate the current status of marine fish diseases in cobia and grouper cage culture in Nam Du islands, Kien Hai district, Kien Giang province. Cobia cage culture (n = 25) and grouper cage culture farmers (n = 25) were directly interviewed from October to December 2013. The results showed that the diseases on cobia and grouper yearly occurred but mainly in two periods of April - May and July to September. The main diseases were reported during cobia culture including ulceration (72%), hemorrhage (64%) and exophthalmia (100%). Parasitic infection was also reported. Chemical was not commonly used during culture period, but antibiotics were used to treat the bacterial diseases. The most common antibiotics were tetracycline, streptomycin, rifamycin and oxytetracycline. Farmers reported grouper diseases comprising ulceration (50%), hemorrhage (38.4%), exophthalmia (11.5%) and parasite infections (23.1%). During husbandry practices, some chemicals (Potassium permanganate, Iodine, Copper sulfate) and antibiotics (rifamycin, oxytetracycline, tetracycline, ampicillin, nutroplex) were limitedly used.